2021
DOI: 10.1002/cac2.12140
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐transplantation cytoreduction does not benefit advanced myelodysplastic syndrome patients after myeloablative transplantation with grafts from family donors

Abstract: Background The role of pre‐hematopoietic stem cell transplantation (HSCT) cytoreduction with either induction chemotherapy (IC) or hypomethylating agents (HMAs) in treating advanced myelodysplastic syndrome (MDS) remains debatable. We aimed to evaluate pre‐HSCT strategies by comparing the endpoints related to disease control between advanced MDS patients with pre‐HSCT cytoreduction and those with best supportive care. Methods We described 228 consecutive advanced MDS patients who received HSCT from a haploiden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…For advanced MDS patients, as opposed to patients with AML derived from MDS (MDS-AML) or AML-MRC, early referral for HSCT is essential, as no benefit in terms of post-HSCT outcomes was correlated with pre-HSCT cytoreduction [ 45 ]. In a study of 228 consecutive advanced MDS patients, Sun et al reported that cytoreduction did not improve 3-year DFS (70.0% vs. 78.2%, p = 0.189) compared to supportive care [ 46 ]. In contrast, Wang et al demonstrated that cytoreduction significantly improved the OS rate (62.2% vs. 20.0%, p = 0.013) in MDS-AML patients but not in MDS-EB2 patients (59.2% vs. 62.9%, p = 0.991) [ 47 ].…”
Section: Indications and Timing Of Allo-hsctmentioning
confidence: 99%
“…For advanced MDS patients, as opposed to patients with AML derived from MDS (MDS-AML) or AML-MRC, early referral for HSCT is essential, as no benefit in terms of post-HSCT outcomes was correlated with pre-HSCT cytoreduction [ 45 ]. In a study of 228 consecutive advanced MDS patients, Sun et al reported that cytoreduction did not improve 3-year DFS (70.0% vs. 78.2%, p = 0.189) compared to supportive care [ 46 ]. In contrast, Wang et al demonstrated that cytoreduction significantly improved the OS rate (62.2% vs. 20.0%, p = 0.013) in MDS-AML patients but not in MDS-EB2 patients (59.2% vs. 62.9%, p = 0.991) [ 47 ].…”
Section: Indications and Timing Of Allo-hsctmentioning
confidence: 99%